VISUALIZATION OF KOREAN ETHNICITY FORMATION IN JAPAN AS A GUARANTEE OF THE ETHNIC IDENTITY - A, Yem N.; A, Tonomura Masaru (Farabi Journal of Social Sciences, 2019)
Ethno cultural education permits to preserve the ethnic identity of the representatives of the ethnic minorities by the way of inclusion to the native language and culture with simultaneous acquisition to the native language and culture with simultaneous acquisition of the values of the domineering culture. The acceptance of the idea of the enthocultural formation of the ethnic minorities means creation of the polyculture system of the education. By that, basic tasks of the ethno cultural education of the ethno cultural formation is oneas preservation of the ethnical identity and deepening of knowledge about own culture. Therefore, there is regulation that condition of the ethnical formation leads toas one of the fundamental basics of the ethnic identity of the ethnos in this case in relation of Koreans to Japanese.Thus, the presence of the ethnic education the status of Korean schools and possibility of the employment upon the ending of the ethnic schools potentially are the guarantee of the preservation of the ethnic identity and pride for them. The last role-plays the diplomatic relations between Japan and two Koreas. The ethnic education serves to be the ‘visual noticeable and significant” and not only on the level of the ethnos and ethical relationship but on the level of social and governmental organizations of the accepted society.